Food and fashion - Marra, Melissa; Way, Elizabeth (Bloomsbury Visual Arts, 2022)
"Food and Fashion accompanies a major exhibition at The Museum at FIT, New York’s only museum dedicated solely to the art of fashion. This beautifully illustrated book featuring over 100 enticing full-color images, from fashion runways to fine art photography and period cookbooks, examines the influence of food culture through the lens of fashion over the last 250 years. It focuses on the ways that food culture has expressed itself in fashion and how these connect to broader socio-cultural change, examining how vital both have been in expressing cultural movements across centuries, and specifically exploring the role food plays in fashionable expression. With its superb selection of images, and thought-provoking and engaging discussion, Food and Fashion appeals to fashion enthusiasts who have an overlapping interest in food and food studies, including scholars and students, those who enjoy the fashion of food, and all who appreciate the visual culture of food, fashion, and art."
Keywords: Geschichte 1770-2020; Kleidung; Ernährung -- Motiv; Lebensmittel -- Motiv; Mode; Ess- und Trinksitte; Fashion / History / Exhibitions; Food / History / Exhibitions; Ausstellungskatalog